Transferência gênica em células espermáticas de Mus musculus e Ramdia quelen - Amaral, Marta Gonçalves (2009)
Transgenic animals have been used as biological models in studies of the genes functions and their mechanisms of action, as well as to improve animal production. Researchers are trying to produce transgenic animals that will be organs donors in xenotransplants. Another use of the transgenic animal is in the production of recombinant proteins for pharmaceutical interest, starting from several tissues and corporal fluids of different animal species. Using TMGT (Testis Mediated Gene Transfer), the efficiency of pEGFP transgene transmission in mice using non surgical TMGT was evaluated, without epididymis electroporation; using transfectants as DMSO, liposomes, and for the first time the DMA. To evaluate the efficiency of non surgical TMGT in F0 the EGFP expression was evaluated in vivo and detection in genome was conducted by PCR analysis. Moreover, we evaluated which transfectants were more efficient in transgene transmission and if it induce histological damage in testis, by histological analysis. EGFP expression was not detected in F0 through the ultraviolet light.The result of the PCR analysis shows that liposomes and DMSO were the best transfectants for pEGFP in F0. The histological analysis shows that injections of DMSO with exogenous DNA could affect the development of the germ cell of seminal tubules. The purpose about SMGT was to evaluate the interaction of the spermatozoa of silver catfish with pEGFP vector. It was observed that the semen after three washes in isosmotic solution and at 1000 x g centrifugation could eliminate seminal plasma proteins and preserve cellular motility. The time of action of DNase in the seminal plasma was 30 minutes, the temperature of action of DNase ranged between 33-53°C and its inhibition was detected at 70°C. In the presence of EDTA 30mM the activity of DNase was inhibited. Through PCR it was detected that in the DNA of the silver catfish s spermatozoids, the amplicon of EGFP at different concentrations of pEGFP vector (5-100 ng/106 spermatozoa). We demonstrate that spermatozoa of the silver catfish need to be washed to remove seminal plasma before contact with exogenous DNA, after several washes exogenous DNA was internalized in spermatozoa.